Policy Image in Urban Governance: Migration Crisis and the City of Zagreb - Poljak, Željko (Scandinavian Journal of Public Administration, 2018)
This paper questions the concept of policy image in terms of urban governance. Policy image is a key concept developed by Baumgartner and Jones in order to explain policy stability and punctuation in the context of punctuated equilibrium theory. When there is a single dominant policy image, it keeps policy in stability, but when there are one or more strong alternative images, it can create punctuation and drastically change certain poli- cies. The author chooses to analyse this concept at an urban level of governance, specifi- cally in the city of Zagreb in Croatia in relation to the migration crisis that occurred in Croatia in late 2015. By using qualitative methodology and a general inductive approach in analysis of interviews that were conducted with city officials and politicians, the author finds just one dominant policy image in terms of different categories which can be associ- ated with the migration crisis and that image is mostly connected with a humanitarian approach. In conclusion, the author argues that this dominant policy image maintained governance in stability in Zagreb during the migration crisis, while stressing the hypothe- sis that this image was present at a national level of governance as well.